The Results of a Randomized Control Trial Evaluation of the SPARK Literacy Program: An Innovative Approach that Pairs One-on-One Tutoring with Family Engagement. Issue 3 (6th July 2021) - Jones, Curtis J.; Christian, Michael
Abstract: This report presents the results of a two-year randomized control trial evaluation of the SPARK foundational literacy program. SPARK is an early grade literacy program developed by Boys & Girls Clubs of Greater Milwaukee that pairs one-on-one tutoring with parent engagement. In 2010, SPARK was awarded an Investing in Innovation (i3) U.S. Department of Education grant to test its impact in seven low-income and low-achieving Milwaukee Public Schools (MPS). In the fall of 2013, 286 students were randomly assigned to receive SPARK for two years and 290 assigned to the control condition. Overall attrition rates ranged from 34.4% to 38.7% and differential attrition rates between SPARK and control students ranged from 1.2% to 3.0%, depending on the outcome. Most participants received a high dosage of both tutoring and family engagement across their two years of participation. Although SPARK had statistically significant positive impacts on literacy development and regular school day attendance, most, if not all, of the impact was realized during the first year of participation. The impact of SPARK was also found to be greatest for students with the greatest need for additional literacy support.